Load limiting control : a handling qualities analysis - Mballo, C.E.; Prasad, J.V.R.; Berger, T. (My University, 2021)
The aim of this paper is to study the impact of two component load limiting controllers (LLC), viz., command limiting LLC and control limiting LLC, on the quantitative handling qualities speci1cations during pitch maneuvers in the forward flight regime. Specifically, the maximum achievable load factor, the pitch attitude quickness, the agility quickness, and the load quickness parameters are used as metrics to quantify the impact of both LLC schemes on the handling qualities performance of the helicopter. The pitch attitude and agility quickness criteria are used to quantify the agility of the helicopter. The load quickness is used to measure the performance of the component load limiting controllers by quantifying the build up of load on the component during maneuvering flight. Results demonstrate that both component load limiting controllers have similar impact on the pitch attitude quickness, load quickness, and maximum achievable load factor. Furthermore, it is observed that the command limiting LLC has less detrimental effect on the agility quickness when compared to the control limiting LLC.